Taking Time Seriously: Implications for Optimal Climate Policy - Michael Grubb; Rutger-Jan Lange; Nicolas Cerkez; Pablo Salas; Jean-Francois Mercure; Ida Sognnaes (Tinbergen Institute, 2020)
Induced innovation and associated issues of path dependence and inertia are of critical importance in the transition to a carbon free economy. We develop a model that, instead of modeling these processes themselves, models the implications of these characteristics and in the process allows us to shed a more nuanced light on this transition phase, an often neglected task. The resulting policy recommendations emphasize the advantages of immediate action and show under what conditions optimal policy might differ from one sector to another. The model thus generates important and policy-relevant insights while seriously considering transition dynamics.
Keywords: C61; O30; Q30; Q42; Q43; Q54; Q58; 330; abatement; DICE; energy economics; inertia; innovation; path dependence; transition